Teacher Training: Tech Savvy Educator Community Service For Teachers In Learning Center, PPMT Parung - Stella Stefany; Rijanto Purbojo (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
Getting into Indonesia roadmap program